COMPARISON OF THE STRENGTH OF POLITICAL COMMUNICATION OF THREE PAIRS IN THE 2024 INDONESIAN PRESIDENTIAL ELECTION: A QUALITATIVE REVIEW OF THE BANDWAGON EFFECT, EXPECTED UTILITY, AND SIMPLE CANDIDATE PREFERENCE MODELS - Iskandar Muda Hasibuan; Morissan, Morissan; Marlinda Irwanti Poernomo (International Journal of Social Science, 2026)
The 2024 Indonesian Presidential Election demonstrated the imbalance in political communication power between the three candidate pairs: Prabowo–Gibran (PRAGIB), Anies–Muhaimin (AMIN), and Ganjar–Mahfud (GAMA). This imbalance is evident in each pair's ability to leverage voter behavior through three models: the bandwagon effect, expected utility, and simple candidate preference as proposed by Abramowitz (1989). This study aims to compare the political communication power of the three candidate pairs in implementing these three models of voter behavior in the 2024 Presidential Election. The study used a descriptive qualitative approach with a focus on the political communication strategies of the three candidate pairs. Data were collected through in-depth interviews with two key informants involved in national political surveys and campaign political communications. Analysis was conducted using comparative analysis techniques to identify patterns of intensity and effectiveness of each pair's communication strategies. The results show that PRAGIB is the most dominant pair in the three models of voter behavior. They succeeded in maximizing the bandwagon effect through mass mobilization, media support, and digital campaigns. In the expected utility model, PRAGIB stands out through concrete program promises that are easily understood by the public. In simple candidate preference, Prabowo's personal image and Gibran's association with President Jokowi generated a simple but highly effective preference. AMIN held a middle ground, with strength in the urban-educated segment but limited grassroots reach. GAMA held the weakest position in all three models due to its inconsistent narrative, image, and mobilization strategy. This research confirms that the dominance of political communication was a key factor in PRAGIB's electoral success in the 2024 presidential election.